The Effect of Digital Leadership and Transformational Leadership on Employee Performance - Paulina, Oshi (Review: Journal of Multidisciplinary in Social Sciences, 2023)
Human resources are the most meaningful aspect because they are the main foundation for the success of a company, the Company needs a qualified, competitive and superior workforce to achieve its goals. Performance is very important for management to evaluate performance in achieving company goals and planning for the future. This study aims to determine how much influence digital leadership and transformational leadership have on employee performance. The type of research used is quantitative research and uses random sampling. The population in this study was 140 employees with a sample of 100 employees. The data analysis method in this study uses the Smartpls software application with various tests carried out, including the R Square test and Path Coefficient. Based on the results of the r suare test and path coefficient, it can be said that the digital leadership variable has a positive influence on the performance of PT Denso Manufacturing Indonesia employees, the transformational leadership variable has a positive influence on the performance of PT Denso Manufacturing Indonesia employees.